THE INFLUENCE OF SELECTION AND JOB PLACEMENT ON EMPLOYEE PRODUCTIVITY AT THE STATE ASSETS AND AUCTION OFFICE IN MAKASSAR - Arief Hidayat; Muchriady Muchran; Muhammad Akib (CV. AFDIFAL MAJU BERKAH, 2024)
This research is a quantitative descriptive study aiming to understand and analyze the impact of selection and job placement on employee productivity at the State Assets and Auction Office in Makassar. The data collecting methods used in this research include observation, questionnaires, and documentation. The population and sample used in this research consist of 40 respondents. The research result through statistical calculations using the Statistical Package for the Social Science (SPSS) version 27 regarding the influence of selection and job placement on employee productivity at assets and auction office in Makassar which was discussed in the previous chapters, the author draws the important conclusion that selection and job placement have a positive and significant on employee productivity. The result obtained for the selection variable (X1) against employee productivity (Y) show with a significance value of X1 against Y being 0.039, which is less than the value of alpha, that is 0.05 (0.039 < 0.05) and job placement variable (X2) against employee productivity (Y) show a significance value of X2 against Y being 0.009, which is also less than the value of alpha, that is 0.05 (0.009 < 0.05).